Strategi Produk Rekayasa Umum untuk Meningkatkan Market Share Dalam Negeri dengan Metode Delphi - Pribadi, Olin Lintang (IQTISHODUNA, 2020)
This study aims to determine the cause of the low market share of general engineering products at PT PAL Indonesia. Market share analysis is considered important in winning business competition. The study uses qualitative descriptive methods and subject data in the form of opinions, attitudes, experiences or characteristics of a person or group of people who are the research subjects or informants. Source of data used are primary data derived from informant interviews and secondary data derived from supporting documents relevant to the study. To find out the root of the problem using the technique of root causes analysis with the fishbone method and find alternative solutions to the problem with the Delphi method in the form of a questionnaire to the experts. The results of the study explained that the low market share of general engineering products is found in every indicator of fishbone, namely: machine, method, material, manpower, measurement and mother nature. And in the opinion of the experts there is no significant difference of opinion in providing alternative solutions to every problem on the fishbone indicator. So the company can be used in making policies.